Anote on the geodesic-ray property in manifolds without conjugate points - Saleh, Wedad; Kilicman, Adem (Academic Publications, 2015)
Let Wn be a C∞ complete, simply connected n-dimensional Riemannian manifold without conjugate points. The relationship between geodesic-ray property, starshapedness and convexity are established in Wn. Furthermore, some examples are given.